Genetic variability in biometrical traits in watermelon (Citrullus lanatus) - RAJENDRAN, P C; THAMBURAJ, S (The Indian Journal of Agricultural Sciences, 2013)
The range of variability components, heritability and expected genetic advance in a group of 30 genotypes of watermelon [Cilrutlus [lanatus (Thunb.) Mansf.] was studied during 1986 and 1987. The seasonal influence was significant for all the characters except number of seeds/fruit.Â· Uigh genetic variability was observed in the genotypes included in this study. High heritability and high genetic advance for 100-seed weight. average fruit weight, yield/vine arid number of seeds/fruit were the most reliable traits’ for selection.